Reflexión crítica sobre el brutalismo - Casado López, Guillermo (Revista Científica de Arquitectura y Urbanismo, 2019)
RESUMEN: El vacío teórico alrededor del brutalismo no ha permitido establecer una definición ni unacaracterización claras. El hecho indiscutible es quela Unité d’Habitation de Marsella (1947-1952) de LeCorbusier es el punto de partida, siendo de especialrelevancia el uso del apelativo “bruto” que utilizó elarquitecto para describir su aspecto material. Estainvestigación y revisión teórica parte de la hipótesis de que el brutalismo es una peculiaridad dentro delconcepto de sinceridad constructiva, siendo necesariomarcar sus límites y alcances. Mediante la revisiónde los documentos teóricos y críticos, así como de laUnité d’Habitation, se realiza una aproximación a una definición actualizada del brutalismo. PALABRAS CLAVE: brutalismo, crítica, teoría, sinceridadconstructiva, materiales brutos, Unité d’Habitation, Le Corbusier A Critical ReflectiononBrutalism ABSTRACT: The theoretical vacuum around Brutalism has been responsible for the lack of a clear definition of its paradigm. It is indisputable that the Unité d’Habitation at Marseille (1947-1952), designed by Le Corbusier, is the first brutalist building, and of particular relevance the fact that the architect employed the word “brut” in order to describe the building’s material aspect. This theoretical investigation begins with the hypothesis that Brutalism presents a peculiarity within the concept of honesty in construction; in order to approach a definition it is, therefore, necessary to establish its limits. Through a review of the pertinent theoretical and critical documents as well as of the Unité d’Habitation, this article proposes an up-to-date definition of Brutalism. KEYWORDS: Brutalism, criticism, theory, honesty in construction, raw materials, Unité d’Habitation, Le Corbusier